The effect of destination attractiveness on destination attachment and its impact on tourist sustainable behavior - Sri Astuti Pratminingsih; Ahmad Johan; Imanirrahma Salsabil (Jurnal Siasat Bisnis, 2022)
Purpose – In gaining competitive advantage in the tourism context, Bandung City needs a good marketing strategy. This study aims to determine the influence of destination attractiveness on destination attachment and its impact on tourist sustainable behavior in Bandung, West Java.